2012
DOI: 10.1504/gber.2012.047806
|View full text |Cite
|
Sign up to set email alerts
|

The effects of work sampling and feedback on individuals' work- and safety-related behaviour prior to, during, and after observer presence

Abstract: Work sampling has been demonstrated to be an effective tool for supervisors to motivate and enhance subordinates' work and safety performance. However, the effectiveness of work sampling has been questioned due to data being derived solely from direct observation when supervisors are present. The purpose of the current study is to investigate the effects of observer presence over several weeks on individuals' work-and safety-related behaviour prior to, during, and after direct observation. Additionally, this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…These communications are a subset of the overall communication produced by an individual. In addition to validating the hypothesis that gender has an effect on emotions expressed in an enterprise social network ( H1a ), this study’s findings support other work discussing the problematic validity of self-reported and direct observation-based behavioral research (Heine et al , 2008; Lebbon, 2009; Mason et al , 2007).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These communications are a subset of the overall communication produced by an individual. In addition to validating the hypothesis that gender has an effect on emotions expressed in an enterprise social network ( H1a ), this study’s findings support other work discussing the problematic validity of self-reported and direct observation-based behavioral research (Heine et al , 2008; Lebbon, 2009; Mason et al , 2007).…”
Section: Discussionsupporting
confidence: 85%
“…Some of these methods have problematic validity. For instance, it has been shown that self-reported surveys have little value for reporting undesirable behavior (Heine et al , 2008; Mason et al , 2007), and that an observer’s presence can cause participants to behave differently (Lebbon, 2009). For these reasons, indirect observation often is preferable for behavior analysis.…”
Section: Literature Reviewmentioning
confidence: 99%